A Human Face to Technology? – Digital Exams are Coming - Dávid, Gergely A. (Working Papers in Language Pedagogy, 2020)
Technological development has reached a point where computerised foreign language testing is possible as well as desirable. It was not caused by the pandemic, which only speeded up development as all the elements of digital, then online testing were already in place. Technological developments are doubly interesting because they also appear to militate against communicative language testing, the prevailing orthodoxy in the field for the past forty years. At the same time, the field of language testing also faces other challenges, such as a language tests becoming less of a social act, stakeholders functioning in changing roles and last but not least, measurement itself is facing a challenge from business logic.